TYPES OF FREEDOM IN FRANZ KAFKA’S THE METAMORPHOSIS:AN EXISTENTIALIST PERSPECTIVE: Nur Wahyuni - JIIP, Redaksi (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2020)
The purposes of this study are: (1) to identify the types of freedom in the novel, (2) to describe how freedom is depicted in the novel, and (3) to reveal the underlying reason why Franz Kafka addressed individual freedom in the novel. This study uses descriptive qualitative method. This method is intended to get a clear picture of the object to be analyzed. The data was collected in the form of words contained in the novel. The technique of data collection was note-taking. Based on the analysis, there are two types of freedom in the Franz Kafka’s novels, namely Freedom From and Freedom To. Freedom described through characters, through setting and through style. Freedom is something that is expected by every individual without exception, because with the freedom every individual was capable of doing anything in life without the intervention of others. This studies also found that the world view of Kafka in creating The Metamorphosis novel was the of thought arising from the desire to be free from all the authoritarian acts.